Perception On Digital Competence In Social Media Practice Among Creative Arts Students In Institutions Of Higher Learning In Penang - Lim, Jing Yi (2019)
Perception on digital competence of creative arts students plays an important role as their social media practices will foster their learning as well as expose them to risks and opportunities. This study aims to identify creative arts students' digital competence focusing on three core components that include perception on (i) instrumental skills and knowledge, (ii) advanced skills and knowledge; and (iii) attitudes for skills and knowledge application. This study employs a mixed methodology which gathered the perceptions of creative arts students, creative arts lecturers and creative industry practitioners on creative arts students' digital competence. Quantitative findings of the study reveal that creative arts students are satisfied with their own digital competence. Meanwhile, the qualitative findings show that creative arts students are very positive about their own instrumental and advanced skills. However, creative arts lecturers and creative industry practitioners perceive differently. While institutions of higher learning have made much effort to assist and guide creative arts students to elevate their digital competence, creative arts lecturers noted that not all students are digitally competent. Meanwhile, creative industry practitioners perceive that creative arts students' digital competence is weak in general and are not competent in the creative industry. In conclusion, this study suggests that the institutions of higher learning engage creative arts students seriously in digital competence by encouraging good practices in social media, and in building links with the creative industry.